Identification of five partial ABC genes in the liver of the Antarctic fish Trematomus bernacchii and sensitivity of ABCB1 and ABCC2 to Cd exposure - Zucchi, Sara; Corsi, I.; Luckenbach, Till; Bard, S.M.; Regoli, F.; Focardi, S. (Environmental Pollution, 2010)
Several ABC transporters have been characterized from many aquatic organisms, but no information is yet available for Antarctic fish. The aim of this work was to identify the expression of genes for ABC proteins in Trematomus bernacchii, a bioindicator species of the Southern Ocean. Partial cDNA sequences of ABCB1, ABCC1, ABCC2, ABCC4 and ABCC9 were cloned from liver. Using RACE technology, 3.5 and 2.2 kb contigs were obtained for ABCB1 and ABCC2. Considering the elevated natural bioavailability of cadmium at Terra Nova Bay, responsiveness of ABCB1 and ABCC2 to this element was investigated under laboratory conditions. ABCB1 and ABCC2 mRNA levels were approximately four-fold higher in Cd-exposed fish compared to the controls. Induction of ABCB1 protein was also found by western blot. This study provides the first identification of five ABC genes in the liver of an Antarctic key species, some of which may be involved in cellular detoxification. The presence of five partial sequences showing homology with ABC transporters and the sensitivity of ABCB1 and ABCC2 toward cadmium were determined in the liver of T. bernacchii.